Genetic Characterization of Seoul Virus in the Seaport of Cotonou, Benin - Castel, Guillaume; Kant, Ravi; Badou, Sylvestre; Etougbétché, Jonas; Dossou, Henri-Joël; Gauthier, Philippe; Houéménou, Gualbert; Smura, Teemu; Sironen, Tarja; Dobigny, Gauthier (Emerging infectious diseases, 2021)
Seoul virus is a zoonotic pathogen carried by the brown rat Rattus norvegicus. Information on its circulation in Africa is limited. In this study, the virus was detected in 37.5% of brown rats captured in the Autonomous Port of Cotonou, Benin. Phylogenetic analyses place this virus in Seoul virus lineage 7.